Programa de Extensão Universitária: uma análise das dificuldades da execução - Borges, Lorena de Melo (2017)
This research aims to analyze the causes that hinder the execution of the resource of the University Extension Program (PROEXT) for the acquisition of material within the Federal University of Paraíba (UFPB). The purpose of PROEXT is to finance projects and programs for the extension of Public Higher Education Institutions (IPES) through a selection made annually by the Ministry of Education (MEC). In the context of the UFPB, it was verified that between 2013 and 2016 the UFPB ceased to receive R$ 2.354.964,78 in material, including permanent materials that are incorporated into the institution's equity. Such a scenario signals the distancing of the execution of the PROEXT budget in the scope of the UFPB from quality criteria, since the purpose is not being fully fulfilled. As a theoretical reference the present work is based on the theory about the public budget, since the resource comes from federal budget, and on the theory of Quality Management, bringing conceptions of the quality theory for the execution of the resource. The research is classified as exploratory, and the means of investigation is classified as field research and bibliographical. It was decided to limit the timeframe of this work to the years 2015 and 2016. The data collection was done through closed questionnaires applied to the research sample defined from the teaching staff and administrative technicians that are part of the execution of the PROEXT. The questionnaires were elaborated using a Likert-type scale and for the treatment of the collected data, statistical techniques were used. In order to aid in the analysis of the causes, the cause and effect diagram was used as a quality tool. As a result of the analysis of the causes, it was verified the weakness of the UFPB in conducting the management of the PROEXT budget resource, configuring an internal environment which is very vulnerable to external factors due to the absence of planning. It is necessary to create institutional conditions which are favorable to implementation, and only from the strengthening of internal management can one fully know the impacts of factors external to the execution.